Crop physiology : applications for genetic improvement and agronomy - Sadras, Victor; Calderini, Daniel (Academic Press, 2009)
the patterns of land use driven by both climate change and the need to develop crop-based sources of energy, and the environmental and social aspects of agricultural sustainability. Hence, this book compiles a multi-authored perspective on the ways in which crop physiology could be integrated with other disciplines. With a focus on genetic improvement and agronomy, this book addresses the challenges of environmentally sound production of bulk and quality food, fodder, fibre and energy which will be faced over the next decade." -- Publisher's description.